Prevalence and Associated Factors of Hypertension among Adults in Rural Nepal: A Community Based Study - Chataut, J.; Khanal, K.; Manandhar, K (Kathmandu University Medical Journal, 2017)
Background Hypertension is a major health problem throughout the world and is one of the major risk factors for cardiovascular mortality. It is important to detect and manage prehypertension and hypertension to reduce the risk of correlated complications especially cardiovascular diseases. Objective The objective of the study was to find the prevalence and risk factors of hypertension among the adults in rural Nepal. Method A community based cross-sectional study was conducted among 648 respondents. The information was obtained using pre-tested questionnaire which included demographic information of individuals and other risk factors like alcohol and tobacco use, physical activity and diet preference. Height, weight and blood pressure were recorded and hypertension was defined as per Joint National Committee (JNC) VII guidelines. Result The overall prevalence of hypertension was 20.5 % and pre-hypertension was 46.6%. The males had higher prevalence of hypertension (30.6%) compared to females (13.8%). Bivariate analysis showed male gender, smoking and non vegetarian diet have association with hypertension. Male gender [OR 2.50 (1.68 – 3.74)] and non vegetarian diet [OR 0.11 (0.01 – 0.85)] were found to be significantly associated with hypertension in multivariate analysis. Conclusion The prevalence of hypertension and prehypertension was high in the study population. In absence of life style modification and risk reduction the individuals categorized as prehypertension have great risk of developing hypertension in the future which may pose a great challenge in the future. Hence, there is a big scope for screening and primary prevention strategies to curb the epidemic of hypertension.